A new species of Urocleidoides (Monogenoidea: Dactylogyridae) parasite of Psectrogaster amazonica (Characiformes: Curimatidae) and Caenotropus labyrinthicus (Characiformes: Chilodontidae) from Tocantins river, Maranhão state, Brazil with checklist of the genus - Miranda Bezerra, Carine Almeida (2023)
Parasites are important components of global biodiversity and among them, the Monogenoidea stands out, as parasites of fishes, commonly affecting the gills of their hosts. The aim of the present study was to analyze the presence of species of Urocleidoides parasitizing characiform fishes from the Tocantins River. During the study, specimens of Psectrogaster amazonica Eigenmann & Eigenmann and Caenotropus labyrinthicus (Kner) were collected from the urban zone of the municipality of Imperatriz, state of Maranhão. The gills of the fishes were removed and placed in vials containing hot water (65°C), and posteriorly, absolute ethanol was added to reach a concentration of 70%. A new species of Urocleidoides was described parasitizing both hosts. Urocleidoides psectrogasteri n. sp. can be distinguished by its congeners species principally by the morphology of the MCO.  Besides, the known species U. tocantinensis, also was founded parasitizing C. labyrinthicus, which was reported as a new host for this species. In addition, a checklist containing all species of Urocleidoides is presented to compile the known data on this monogenoid genus.